Sexual Violence (IntechOpen, 2024)
Sexual violence is a multifaceted crime and a global health problem. It is a crime that can happen to anyone, including young and old, male and female, rich and poor. Sexual violence persists due to several variables, including abuse history and a society’s tolerance of the crime. Additionally, belief systems, cultural norms, and legal systems create environments that allow abusers to escape detection. This book addresses sexual violence myths, belief systems, and the media’s role in perpetuating sexual violence. It also examines the role of social media in facilitating sexual crimes, particularly sex trafficking. Finally, this book examines the work of community stakeholders in addressing and treating individuals who have been sexually victimized and the coping mechanisms of sexually traumatized adult women.